Stress-Sensing Method via Laser-Generated Ultrasound Wave Using Candle Soot Nanoparticle Composite - Kim, Howuk (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2020)
This article aims to develop a semi-noncontact stress-sensing system using a laser-generated ultrasound (LGU) wave assisted by candle soot nanoparticle (CSNP) composite. While the acoustoelastic effect is commonly targeted to measure the stress level, efforts to combine it with the LGU wave signal have been lacking due to weak signal intensity. In this study, the CSNP-based transducer is designed to potentiate the photoacoustic energy conversion. To demonstrate the wave propagation with the designed parameters, a numerical simulation was first conducted. The experimental results showed that a laser intensity of 6.5 mJ/cm2 was enough to generate the subsurface longitudinal (SSL) wave from the CSNP composite transducer. The normal beam projection is the most effective wave-generation method, exhibiting the highest signal magnitude compared with inclined projection cases. Finally, the laser-assisted stress-sensing system was assessed by increasing the internal pressure of an air tank. The sensitivity of the developed sensor system was estimated to be 0.296 ns/MPa, showing a correlation of 0.983 with the theoretical prediction. The proposed sensing system can be used to monitor the structural integrity of nuclear power plants